English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

rewrite the expression
log base 2 of x +3 log base 2 of y - 5 log base 2 of z
as a single logarithm log bas 2 of A

2007-10-30 13:59:49 · 3 answers · asked by star baller 360 5 in Science & Mathematics Mathematics

it said it wrong please help

2007-10-30 14:13:17 · update #1

3 answers

First rule of logs:
k log x = log (x^k)

So that simplifies your equation to:
log[2] x + log[2] (y^3) - log[2] (z^5)

Next rules are:
log a + log b = log(ab)
log c - log d = log(c/d)

Your final equation should be:
log[2] ( x y^3 / z^5 )

2007-10-30 14:06:10 · answer #1 · answered by Puzzling 7 · 0 0

log(base 2) (x) + 3 log(base 2) y + log(base 2) z^-5

= log(base 2) (x)(y^3)(z^-5) (rule : log(a)(b) = log a + log b)
(rule : log a^b = b log(a))


= log(base 2) xy^3/z^5)

2007-10-30 21:06:19 · answer #2 · answered by frank 7 · 0 0

in base 2:

= log x + 3log y - 5log z
= (base 2) log (xy^3)/(z^5)

Hope this helps :)

2007-10-30 21:08:45 · answer #3 · answered by thejoketh 1 · 0 0

fedest.com, questions and answers